Cervical modifications after pessary placement in singleton pregnancies with maternal short cervical length: 2D and 3D ultrasound evaluation. (13th June 2019) - Mendoza Cobaleda, Manel; Ribera, Irene; Maiz, Nerea; Goya, Maria; Carreras, Elena
Abstract: Introduction: The use of a pessary proved to prevent preterm birth in asymptomatic women with mid‐trimester short cervical length (CL); however, the precise mechanisms by which the pessary confers its benefit remain unclear. The aim of this study was to evaluate multiple cervical characteristics assessed by 2‐dimensional and 3‐dimensional ultrasound before and after placement of a cervical pessary to ascertain its mechanism of action. Material and methods: In this prospective cohort study, we assessed the cervical characteristics in singleton pregnancies with maternal short CL and compared them with matched reference women with normal CL. The variables evaluated were: CL, uterocervical angles, cervical consistency indices (cervical consistency index and CL consistency index), cervical volume and vascular indices. All variables were re‐assessed immediately after pessary placement and 4‐6 weeks later in all participants. Mann‐Whitney U test was used to assess differences between groups and paired samples t test for comparisons in two different examinations in the same women. The aim of this study was to evaluate multiple cervical ultrasound variables before and after the placement of a cervical pessary and compare the evolution of these variables with a reference group with normal CL to better understand the device's mechanism of action. Results: Thirty‐three women with short CL and 24 reference women with normal CL were enrolled. At the time of enrollment, gestational age and maternal baseline characteristics did not differ between groups. Immediately after pessary placement, CL increased, uterocervical angles were narrower and cervical consistency increased significantly. When the magnitude of change in cervical variables was compared over time between the reference group and the study group, median CL had increased in the study group (1.47 mm) but it had shortened in the reference group (−2.56 mm). These inverse trends were statistically significant ( P  =   0.006). Conclusions: Cervical pessary reduces both uterocervical angles and corrects cervical angulation by pushing the cervix up toward the uterus. Maintaining the cervix aligned to the uterine axis leads to reduced cervical tissue stretch, so avoiding further cervical shortening. All these changes were present after pessary placement; however, the clinical implications of these findings remain unknown.